A STUDY ON VOCABULARY MASTERY OF FIRST YEAR STUDENTS OF SMK LABOR BINAAN FKIP UNIVERSITAS RIAU - Akbar Dermawan Sinaga; Hadriana Hadriana; Muhammad Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The aim of this research is to find out the level of the first year students of SMK Labor Binaan FKIP Universitas Riau in vocabulary mastery. The sample of this research is ADP 2 which was choosen by using cluster random sampling technique. The number of the student is 30 students. The data obtained by giving multiple choice test. About the test, the students are asked to choose the appropriate vocabulary based on the context of the test. The test consist of 7 indicators of vocabulary. There are synonym, antonym, collocation word, noun, verb, adjective and adverb. The result shows that the students score in vocabulary mastery is 54.79, and the students have problem in verb with mean score 32.26 % of correct answers and adverb with mean score 44.99%. In conclusion, from the result above shows that the students’ vocabulary mastery level of SMK Labor Binaan FKIP Universitas Riau is in mediocre level..Key Words: Study, Vocabulary, Mastery